2020
DOI: 10.1097/mlr.0000000000001397
|View full text |Cite
|
Sign up to set email alerts
|

Associations of 4 Nurse Staffing Practices With Hospital Mortality

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 44 publications
(60 reference statements)
0
45
0
Order By: Relevance
“…Using digitized payroll and patient data, we examined how shift‐to‐shift variations in several nurse staffing practices were related to the risk of all‐cause in‐hospital death. We found that every 5.0% increase in the cumulative proportion of understaffed shifts since hospital admission was associated with a 1.0% increase in the risk of death (Rochefort et al., 2020). Moreover, we noted that every 5.0% increase in the cumulative proportion of worked hours by baccalaureate‐prepared Registered Nurses (RNs) decreased the risk of death by 2.0%.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Using digitized payroll and patient data, we examined how shift‐to‐shift variations in several nurse staffing practices were related to the risk of all‐cause in‐hospital death. We found that every 5.0% increase in the cumulative proportion of understaffed shifts since hospital admission was associated with a 1.0% increase in the risk of death (Rochefort et al., 2020). Moreover, we noted that every 5.0% increase in the cumulative proportion of worked hours by baccalaureate‐prepared Registered Nurses (RNs) decreased the risk of death by 2.0%.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, we noted that every 5.0% increase in the cumulative proportion of worked hours by baccalaureate‐prepared Registered Nurses (RNs) decreased the risk of death by 2.0%. Last, we found that RNs’ levels of experience and the proportion of non‐RN staff were not related to the risk of death (Rochefort et al., 2020).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations